HUBUNGAN ANTARA INTERAKSI KNOWLEDGE MANAGEMENT, SUMBERDAYA MANUSIA DAN INKLUSI KEUANGAN DENGAN KINERJA UMKM - Basuki Basuki; Rahmi Widyanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Entrepreneurship is very important for the economy of a country, because entrepreneurs areone of the drivers of the strength of the country's economic growth. The SMEs sector is a sectorthat has been able to survive the economic crisis throughout the history of the economic crisis thatoccurred in Indonesia. This is because the performance of SMEs is supported by a number ofenvironmental factors, such as the support from BUMN and BUMD as well as from the bankingsector.The objective this study to present a conceptual framework that proposes the proposition ofthe positive influence of human resources and knowledge management on the performance ofSMEs in the province of South Kalimantan Indonesia through comparative qualitative researchmethods. Consequently, access to finance moderates the relationship between Human Resourcesand MSME performance and access to finance moderates the relationship between KnowledgeManagement and MSMEs performance. In conclusion, the role of competition in determining theperformance of SMEs requires a study that examines competition outside the conventionalcompetitive approach which directly affects performance.